Inverse Abdominoplasty An Illustrated Guide - Tiryaki, Kemal Tunc.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Written by international experts, this book describes different techniques for abdominoplasty. It starts with a functional anatomy description of the abdomen, followed by a brief overview of current techniques. With the help of numerous illustrations, the reader will gain detailed knowledge of how to perform the inverse full abdominoplasty, the inverse mini abdominoplasty (with and without floating umbilicus) and the secondary inverse abdominoplasty. Lastly, ancillary procedures that can be used in conjunction with inverse abdominoplasty are discussed. By also addressing the potential complications of this surgical procedure, the book offers essential guidelines for surgeons dealing with a variety of problems in the surgery of the abdominal area. Although abdominoplasty is one of the oldest procedures in plastic surgery, new approaches like high lateral tension abdominoplasty have refined the technique and its aesthetic outcomes. Still, problems remain like the length of the procedure, difficulties of dissection of long flaps, lack of elasticity in the flaps due to previous surgery, scars at the surgical site, unfavorable aesthetic outcomes, and variable challenges during the postoperative period, like wound healing and pain. Particularly, secondary abdominal surgery remains a technical challenge, from decision to application.
Functional anatomy of the abdomen: The surgeons perspective -- Anesthesia and algology in abdominal surgery -- Patient selection and differential diagnosis simplified -- The Theory of Inverse abdominoplasty -- The Technique of Inverse Abdominoplasty.-Inverse Mini-abdominoplasty -- Abdominoplasty as a combined procedure -- Umbicus management and creating a neo-umblicus -- Abdominal wall hernias and their treatment with inverse abdominoplasty -- Prevention and management of abdominoplasty complications -- Postoperative care: From good to great.
Keywords: Medicine; Plastic surgery; Medicine & Public Health; Plastic surgery